2017
DOI: 10.1007/s13312-017-1127-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conventional and LED phototherapy on the antioxidant-oxidant status in preterm neonates with jaundice

Abstract: Both modes increased oxidative stress index; however, conventional phototherapy resulted in higher oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Interesting study done exclusively among preterm neonates, compared antioxidant-oxidant parameters following conventional and LED phototherapy, both conventional and LED phototherapy resulted in increased oxidative stress index. However, derangement of antioxidant-oxidant parameters was more pronounced after conventional as compared to LED phototherapy [13] . Unconjugated bilirubin is considered a potent antioxidant when present at moderate levels.…”
Section: Discussionmentioning
confidence: 89%
“…Interesting study done exclusively among preterm neonates, compared antioxidant-oxidant parameters following conventional and LED phototherapy, both conventional and LED phototherapy resulted in increased oxidative stress index. However, derangement of antioxidant-oxidant parameters was more pronounced after conventional as compared to LED phototherapy [13] . Unconjugated bilirubin is considered a potent antioxidant when present at moderate levels.…”
Section: Discussionmentioning
confidence: 89%
“…9,19 It has been shown in some studies that after phototherapy, their ability to fight increased and oxidative stress is weakened by reducing the levels of antioxidants such as glutathione and ascorbic acid. [20][21][22] Dynamic thiol-disulfide homeostasis in newborns has an important role in many oxidant-antioxidant mechanisms such as detoxification, antioxidant protection, regulation of enzyme activity. 23 Thiol-disulfide homeostasis has been associated with diseases that increased inflammation such as neonatal sepsis and hepatitis, and conditions that increase stress such as hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Kale et al 12 found that both conventional phototherapy with blue fluorescent lights and intensive LED phototherapy significantly decreased serum TAC and increased OSI values. Allam et al 15 demonstrated that both conventional and LED phototherapy resulted in increased OSI values; however, alteration of antioxidant/oxidant parameters was more pronounced after conventional than after LED phototherapy. Another study reported increased oxidative stress following conventional phototherapy, but found no significant change following LED phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, some reports have indicated that phototherapy may cause oxidative stress, lipid peroxidation, and DNA damage. [9][10][11][12][13][14][15] The Turkish Journal of Pediatrics • September-October 2019 Moreover, neonates have a limited antioxidant protective capacity, and oxidative damage has an important role in the pathogenesis of many diseases in the newborn period. 16 Therefore, this study aimed to assess the impacts of conventional and LED phototherapy on DNA damage, total oxidant status (TOS), and total antioxidant capacity (TAC) in jaundiced newborns.…”
mentioning
confidence: 99%